2014
DOI: 10.1515/hf-2014-0097
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen plasma treatment of bamboo fibers (BF) and its effects on the static and dynamic mechanical properties of BF-unsaturated polyester composites

Abstract: A novel method for the preparation of bamboo fibers (BF) has been investigated that includes crushing, rolling, and other combing techniques with 1,4-butanediol as a dispersant. The fibers were treated by oxygen plasma to improve their interfacial adhesion to unsaturated polyester (UPE) resins. Composites were prepared from the plasma treated fibers (BF tr ) and UPE by hand layup compression molding. BF tr significantly increased the tensile strength, flexural strength, and flexural modulus of the resulting BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The results showed an increase in oxygen content and a decrease in carbon content because plasma treatment with inert gas improved the surface activity of the fibers, allowing free radicals to react with oxygen to form peroxides, and the atomic percentage of carbon decreased as the atomic percentage of oxygen increased [ 11 ]. The presence of ROS caused an oxidation reaction that etched and oxidized the cellulose surface, resulting in the removal of hemicellulose, lignin, and amorphous portions of the fiber surface [ 8 , 37 ]. These results are consistent with the FTIR analysis results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed an increase in oxygen content and a decrease in carbon content because plasma treatment with inert gas improved the surface activity of the fibers, allowing free radicals to react with oxygen to form peroxides, and the atomic percentage of carbon decreased as the atomic percentage of oxygen increased [ 11 ]. The presence of ROS caused an oxidation reaction that etched and oxidized the cellulose surface, resulting in the removal of hemicellulose, lignin, and amorphous portions of the fiber surface [ 8 , 37 ]. These results are consistent with the FTIR analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…XPS analysis was performed to determine the elemental bonding of the carbon and oxygen atoms and to compare the energy levels and fiber intensities of the untreated and plasma-treated fiber samples ( Figure 5 ). The XPS spectrum of carbon atoms on the fiber surface showed the highest intensity, where energy levels of approximately 285.0, 286.7, and 287.5 eV indicate the characteristics of C1s forming C–C or C–H, C–O, and C–OH bonds, respectively [ 8 , 62 , 63 ]. The C–OH bond is absent in the untreated plasma fibers, but it appears after the plasma treatment of the BFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-frequency heating technique can accelerate the heating and curing rates, but no chemical reactions occur between the adhesive and the bamboo surface . Surface chemical treatment was used to improve the interfacial adhesion between the fiber interface and the adhesive to improve the mechanical properties of the composite. Studies have shown that the high-voltage electrostatic field (HVEF) treatment has a positive effect on enhancing the bonding and mechanical properties of bamboo and wood. , Accelerated free electrons at HVEF cracked chemical bonds and polarized material surfaces. , Polarized surfaces provided more opportunities to react with adhesives between bonding interphases without considering timelines…”
Section: Introductionmentioning
confidence: 99%